Virtual screening based on molecular docking of possible inhibitors of Covid-19 main protease. (November 2020) - Marinho, Emanuelle Machado; Batista de Andrade Neto, João; Silva, Jacilene; Rocha da Silva, Cecília; Cavalcanti, Bruno Coelho; Marinho, Emmanuel Silva; Nobre Júnior, Hélio Vitoriano
Abstract: Coronavirus (COVID-19) is an enveloped RNA virus that is diversely found in humans and that has now been declared a global pandemic by the World Health Organization. Thus, there is an urgent need to develop effective therapies and vaccines against this disease. In this context, this study aimed to evaluate in silico the molecular interactions of drugs with therapeutic indications for treatment of COVID-19 (Azithromycin, Baricitinib and Hydroxychloroquine) and drugs with similar structures (Chloroquine, Quinacrine and Ruxolitinib) in docking models from the SARS-CoV-2 main protease (M-pro) protein. The results showed that all inhibitors bound to the same enzyme site, more specifically in domain III of the SARS-CoV-2 main protease. Therefore, this study allows proposing the use of baricitinib and quinacrine, in combination with azithromycin; however, these computer simulations are just an initial step for conceiving new projects for the development of antiviral molecules. Highlights: The analysis of molecular docking simulations showed that all inhibitors bound to the same enzyme site. All inhibitors bound in domain III of the SARS-CoV-2 main protease. Were identified in the molecular docking simulations, classified as Hydrogen Bond Strongly Covalent with baricitinib (Asp197 and Leu287), chloroquine (Tyr239), and quinacrine (Tyr239). Were identified in the molecular docking simulations, classified as Hydrogen Bond Moderate Mostly Electrostatic with baricitinib (Lys137), azithromycin (Leu272), hydroxychloroquine (Lys137 e Tyr237), and ruxolitinib (Lys137